Deciphering and engineering tissue folding: A mechanical perspective. (15th October 2021) - Zhu, Yanlun; Deng, Shuai; Zhao, Xiaoyu; Xia, Guanggai; Zhao, Ruike; Chan, Hon Fai
Abstract: The folding of tissues/organs into complex shapes is a common phenomenon that occurs in organisms such as animals and plants, and is both structurally and functionally important. Deciphering the process of tissue folding and applying this knowledge to engineer folded systems would significantly advance the field of tissue engineering. Although early studies focused on investigating the biochemical signaling events that occur during the folding process, the physical or mechanical aspects of the process have received increasing attention in recent years. In this review, we will summarize recent findings on the mechanical aspects of folding and introduce strategies by which folding can be controlled in vitro . Emphasis will be placed on the folding events triggered by mechanical effects at the cellular and tissue levels and on the different cell- and biomaterial-based approaches used to recapitulate folding. Finally, we will provide a perspective on the development of engineering tissue folding toward preclinical and clinical translation. Statement of significance: Tissue folding is a common phenomenon in a variety of organisms including human, and has been shown to serve important structural and functional roles. Understanding how folding forms and applying the concept in tissue engineering would represent an advance of the research field. Recently, the physical or mechanical aspect of tissue folding has gained increasing attention. In this review, we will cover recent findings of the mechanical aspect of folding mechanisms, and introduce strategies to control the folding process in vitro . We will also provide a perspective on the future development of the field towards preclinical and clinical translation of various bio fabrication technologies. Graphical abstract: Image, graphical abstract